An Analysis of Buffer Solution Topics in Chemistry Textbooks: Application of the 4 Step Teaching Material Development Criteria - Asmiati, Lisya; Sari, Diah Kartika; Sanjaya, Sanjaya; Sukaryawan, Made; Adhiya, Eka (Jurnal Tadris Kimiya, 2024)
Buffer solution content in Chemistry textbooks plays a significant role in achieving these educational objectives. This study aims to analyze buffer solution material in class XI Chemistry textbooks using the 4S TMD selection criteria, focusing on curriculum consistency, concept accuracy, and value education. A qualitative evaluative approach was employed, comparing the data collected from two textbooks (Book A and Book B) against established standards. The evaluation covered the scope and depth of the material, the accuracy of concepts, and the integration of values. The analysis found that both textbooks included six relevant concept labels, though Book B contained one overly general label. Regarding concept depth, Book A had two concepts with insufficient depth, while Book B had one overly shallow concept and one excessively detailed. Both books achieved the standard for concept accuracy. For value education, Book A integrated six core values, such as discipline and responsibility, while Book B incorporated eleven values, including creativity, democracy, and honesty. The findings suggest that Book A aligns more closely with the 4S TMD evaluation criteria than Book B. This highlights the importance of balancing curriculum alignment, conceptual depth, and value integration in educational materials.